Fabrication of cactus-like CNT/SiO2/MoO3 ternary composites for superior lithium storage. (15th February 2021) - Zheng, Yuhuan; Liu, Zhikang; Liu, Bin; Wang, Shan; Xiong, Chuanxi
Abstract: Advanced electrode materials with high rate capability and long cycling stability are highly pursued for high-performance lithium-ion batteries (LIBs). In this study, cactus-like CNT/SiO2 /MoO3 composites are synthesized via self-assembly followed by in-situ carbonization, wherein the CNT, SiO2, and MoO3 are uniformed distributed. Such unique structure can effectively alleviate the strain during cycling, reduce the Li + diffusion time, and provide more active sites for the interaction of ions, thus allowing much better rate capability. Specifically, CNTs act as the cactus veins to rapidly transport the electrons, while the SiO2 and MoO3 particles located in the cactus leaf-like region are used to store lithium. In addition, the MoO3 can play as a supporter to minimize the change of the whole structure and further stabilize the electrode because of the lower strain during lithiation. As a consequence, the CNT/SiO2 /MoO3 electrode delivers a high specific capacity (700 mAh g −1 at 1000 mA g −1 over 500 cycles) and long cycle life (320 mAh g −1 at 5000 mA g −1 within 800 cycles). It is possible that this research could provide new insights for developing novel anode materials with superior lithium storage capability. Graphical abstract: Image 1 Highlights: Cactus-like CNT/SiO2 /MoO3 composites are synthesized via self-assembly followed by in-situ carbonization. CNTs are uniformly distributed as the cactus-like veins and thus beneficial to rapidly transfer electrons. The SiO2 and MoO3 particles located in the cactus leaf-like region can form an efficient channel for ions transport. The CNT/SiO 2 /MoO 3 electrode shows both high reversible capacity and long cycle life.